Pengaruh Profitabilitas, Leverage, Sales Growth, dan Inventory Intensity terhadap Tax Avoidance - Ani Safitri; Desy Mariani (Jurnal Mutiara Ilmu Akuntansi, 2024)
This study aims to determine the effect of Profitibality, Leverage, Sales Growth, and Inventory Intensity on Tax Avoidance in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019 – 2023 period of 93 companies. The data used in this study were obtained from financial statement data and annual reports. The population in this study are property and real estate sector companies listed on the Indonesian Stock Exchange. The sampling technique used was purposive sampling method and obtained 220 sample data from 44 companies. The analysis technique used in this study is multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) version 22. The results of this study indicate that profitability and Leverage have a negative and Significant effect on Tax Avoidance, while Sales Growth and Inventory Intensity has no effect on Tax Avoidance.